Elastic-plastic stress analysis and expansion of plastic zone in clamped and simply supported thermoplastic-matrix laminated plates with square hole - Arslan, N; Arslan, N; Okumus, F (Elsevier Sci Ltd, 2004)
In the present study, an elastic-plastic stress analysis and the expansion of plastic zone in layers of stainless steel woven fiber-reinforced thermoplastic matrix composite laminated plates with square hole are carried out by using finite element method (FEM) and First-order shear deformation theory for small deformations. A finite element computer program is developed for stress analysis. The laminated plates ([0degrees/thetadegrees](2)) Under uniform transverse loading are formed by stacking four composite layers bonded symmetrically or antisymmetrically. Each layer with constant thickness is meshed into 64 elements and 288 nodes. Loading is gradually increased from yield point of the plate as 0.0001 MPa at each load step. The load steps are chosen as 200-600. The expansions of the plastic zones, the residual stress components, and yield points are calculated according to load steps and orientation angles under clamped and simply supported boundary conditions. The intensity of the residual stress components is maximum near the square hole and clamped supports. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: residual stress; plastic zone